Rehabilitation of pharyngeal dysphagia and spastic dysarthria following acute ischemic stroke: a case study - Johnsirani, R.; Jaya, V.; Janani, S.; P., Thrisha (International Journal of Research in Medical Sciences, 2025)
We present the case of a 49-year-old female with a history of coronary artery disease, hypothyroidism, and prior coronary artery bypass grafting, who presented with slurred speech, left-sided mouth deviation, and difficulty swallowing. Imaging confirmed acute ischemic stroke affecting the left precentral gyrus and left corona radiata. The patient was diagnosed with spastic dysarthria and pharyngeal dysphagia, with severe swallowing difficulties and aspiration. A comprehensive swallowing therapy plan was developed, focusing on both rehabilitative and compensatory techniques. Rehabilitative therapy included exercises like the chin-down posture to improve tongue control and laryngeal closure, the tongue anchor exercise to increase pharyngeal wall pressure, and the Valsalva maneuver to promote safer swallowing. The supraglottic swallow and effortful swallow techniques were introduced to improve bolus clearance and reduce residue. Compensatory strategies such as thermal tactile stimulation, the sour bolus strategy, and the dry gargle technique were applied to improve sensory awareness and swallowing safety. The patient was gradually introduced to different food consistencies, progressing from thickened liquids to a regular diet. After two weeks of therapy, swallowing function significantly improved, with increased oral intake, improved dysphagia severity scores, and a transition to a regular diet. This case emphasizes the importance of targeted swallowing therapy in post-stroke rehabilitation.